TOKSISITAS SENYAWA Β-SITOSTEROL DAN EKSTRAK KULIT BATANG AGLAIA - Riky Riky (STIKES Insan Cendekia Medika Jombang, 2018)
Pacar cina (Aglaia odorata Lour) is a plant that is widely used as an traditional medicine because of natural materials they contain. The study aims to from Pacar cina extracts and toxicity test of each extract and isolated compound by BSLT (Brine Shrimp Lethality Test) method. The method used in the maceration. In this study, the n-hexane, ethyl acetate, methanol extracts and β-sitosterol compound showed toxic effect (LC50 261,17; 110; 266,75 and 100 μg/mL, respectively). The toxicity degree among the three extracts and isolated compound is β-sitosterol > ethyl acetate > n-hexane > methanol.